Characteristics of Possession of the Ball When the Senior and Preparatory Group Perform the Elements of Children's Soccer - Barno Pulatovna Abdullaeva (Zien Journals, 2023)
The article presents the results of research work on teaching football elements in preschool instituitons. Moreover, the results of boys and girls doing simple elements of football are compared statistically.
Keywords: technical football elements; pre-school students; pre-school preparatory groups